Gaya Desain pada Elemen Pembentuk Ruang dan Elemen Transisi Interior Gereja Santo Antonius Purbayan Surakarta - Andereas Pandu Setiawan, Devi Yosin Tjia (Intra, 2013)
Santo Antonius  Purbayan  church  is  the oldestchurch  building  in  Surakarta.  This  heritage building of  DutchColonial  period  was built  in 1916  and  still standing  to this day, and  did not experience  much  changes  in the  architecture  and interior  aspects.  The building is  a historical evidence of an event that  has  the value of  architectural  and  interior.  The  stylescombination  of  space  forming  elements  and  transition  elements in  the  interior  is  very variative, that are  Art  &  Craft,  ArtNouveau,  Art  Deco,  Nieuwe  Bouwen,  and  also to  the European Classical  style  such as  the  church  building at  the first in Europethat  are  Early Christian  style,  Romanesque  and  Gothic.  The combination  of  various  styles  could not be separated  fromaspects of  function  and  meaning  of  a  church  and  has beenadapted to the local climate and conditions.